2003
DOI: 10.1034/j.1600-0854.2003.40206.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Ruffled Border Has Distinct Subdomains for Secretion and Degraded Matrix Uptake

Abstract: Subosteoclastic bone resorption is a result of HCl and proteinase secretion through a late endosome-like bone facing membrane domain called ruffled border. As bone matrix is degraded, it enters osteoclasts' transcytotic vesicles for further processing and is then finally exocytosed to the intercellular space. The present study clarifies the spatial relationship between these vesicle fusion and matrix uptake processes at the ruffled border. Our results show the presence of vacuolar H π -ATPase, small GTPase rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
116
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 63 publications
(69 reference statements)
12
116
0
Order By: Relevance
“…After attachment to bone, the ruffled border secretes enzymes and protons enabling the solubilization and digestion of the bone matrix. Rapid cytoskeletal reorganization is essential for osteoclast function and formation of the specialized membranes (21,35). NMP treatment disrupted actin ring formation in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…After attachment to bone, the ruffled border secretes enzymes and protons enabling the solubilization and digestion of the bone matrix. Rapid cytoskeletal reorganization is essential for osteoclast function and formation of the specialized membranes (21,35). NMP treatment disrupted actin ring formation in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cell type and labelling conditions, a proportion (up to 25%) of the transferrin has a half-life of only 5-7 minutes inside the cell, whereas a larger proportion accumulates in the recycling endosome and it can take more than 60 minutes before these molecules are recycled back to the plasma membrane (Hopkins et al, 1994). In osteoclasts, it has been shown that endocytosed transferrin reaches the ruffled border after 30 minutes of incubation (Mulari et al, 2003;Palokangas et al, 1997), establishing that there is cross-talk between the recycling and late endosome/ ruffled border. However, the amount of transferrin that reaches the ruffled border has not been established.…”
Section: Co-localization Of Dextran With Endocytic Markersmentioning
confidence: 99%
“…This dynamic equilibrium is supported by the finding that basolaterally endocytosed transferrin is found in the area of the ruffled border after 30 minutes of chase (Palokangas et al, 1997). It was also recently suggested that the ruffled border is divided into a peripheral secretory subdomain and a centrally located uptake zone (Mulari et al, 2003). Studies with differentially targeted virus particles, in conjunction with the localization of lysosomeassociated membrane proteins (LAMPs) and the small GTPase Rab7 to this plasma-membrane domain, also indicate a high similarity of the ruffled border to the late-endosome/lysosome compartment (Palokangas et al, 1997;Salo et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once the mineral degradation is underway, the degradation of bone organic matrix (mostly type 1 collagen) can take place. This function is performed by many degradative factors including acid phosphatases (TRAP), matrix metalloproteinases (MMPs) and the lysosomal enzyme cathepsin K, which, like the ion channels necessary for acidification, polarize to the ruffled membrane after osteoclast attachment to the bone, to be as close as possible to the site of action (Mulari et al, 2003) ( Figure 5). …”
Section: Osteoclastic Bone Resorptionmentioning
confidence: 99%